A case of galactosemia misdiagnosed as cow's milk intolerance - Casa Roberto; Ungaro Carla; Acampora Emma; Pignata Claudio; Vajro Pietro; Salerno Mariacarolina; Santamaria Francesca; Parenti Giancarlo (BMC, 2012)
Abstract We report on a female patient affected by galactosemia in whom the diagnosis was obscured by the concomitant presence of manifestations suggesting a cow's milk intolerance. This case exemplifies the problems in reaching a correct diagnosis in patients with metabolic diseases.